Shopee seller marketing strategy in the perspective of Islamic marketing ethics - Rosyada, Mohammad; Palupi, Yuniarsih Endah; Tamamudin, Tamamudin (Universitas Negeri Surabaya, 2023)
This study aims to discuss the marketing strategies of Shopee sellers from the perspective of Islamic marketing ethics. This study uses descriptive qualitative research methods using primary data and secondary data. Data collection techniques are interviews, observations, and documentation conducted with 20 informants of 10 buyers and 10 sellers at Shopee. Promotions attract the attention of Generation Z are attractive product displays, discounts, free shipping, and viewing reviews or ratings of the products they want to buy. From the seller's side, in implementing their marketing strategy, they use the marketing mix concept, namely 4P (product, price, place, promotion), based on what Rasulullah SAW exemplified as a Muslim entrepreneur. That is, the business philosophy built by the owner is based on profit-oriented Sharia business and blessings. The Shopee sellers who became informants in this study were following the theories and concepts of Islamic marketing ethics and had implemented Islamic content consisting of three main things: first, the application of Islamic marketing characteristics; second, the application of Islamic business ethics; third, following the marketing practices of the Prophet Muhammad SAW based on the characteristics of the Prophet Muhammad, namely: Siddiq, Amanah, Fathanah, and Tabligh.